Combined Experimental and Theoretical Approaches to the Molecular Structure of 4-(1-formylnaphthalen-2-yloxy)phthalonitrile - Tereci, H.; Askeroǧlu, I.; Akdemir, N.; Uçar, I.; Büyuk̈güngör, O. (Pergamon-Elsevier Science Ltd, 2012)
The novel compound 4-(1-formylnaphthalen-2-yloxy)phthalonitrile, C 19H10N2O2, has been synthesized and characterized by IR, UV-vis, NMR and X-ray single-crystal determination. The title compound, is built up from two planar groups (naphthalen and phthalonitrile), with a dihedral angle of 64.10(4)° between them. The crystal structure is stabilized by weak C-H⋯O hydrogen-bond and π-π interactions. The structural and spectroscopic data of the compound in the ground state have been calculated using density functional theory (DFT) and Hartree-Fock (HF) with the 6-31G(d,p) basis set. The vibrational study was interpreted in terms of potential energy distribution (PED). The observed wave number in FT-IR spectra was analyzed and assigned to different normal modes of the molecule. Using the TD-DFT and TD-HF methods, electronic absorption spectra of the title compound were predicted and good agreement with the TD-DFT method and the experimental determination was found. Isotropic chemical shifts ( 13C and 1H NMR) were calculated using the gauge-invariant atomic orbital (GIAO) method. The HOMO and LUMO analyses were used to elucidate information regarding charge transfer within the molecule. © 2012 Elsevier B.V. All rights reserved.
Keywords: 13C and 1H NMR; DFT; FT-IR; Phthalonitrile; UV-Vis; X-Ray Diffraction